Secondary Schooling as Preparation for World of Work: Employers Expressed Needs and Curricular Responses - Lemessa Abdi Negesso; Ambissa kenea (Universitas Islam Negeri (UIN) Sulthan Thaha Saifuddin Jambi, 2022)
Abstract The purpose of this study is to examine the linkage between expressed needs of selected employers of secondary school graduates and the secondary school curriculum with the overall aim of examining the relevance of curriculum. Mixed research method was employed. Employers and secondary school textbooks are the major sources of data for the study, with interview and document analysis as tools for data collection, respectively. The findings of the study indicated that the employers perceived time management, teamwork, communication skills, independent work, ability and readiness to learn, and self management are the competencies that are crucial for employees to survive in their organizations. On the other hand, ability to work with others, effective way of communication, appropriate use of work time, self-control, independently solving problems and ability to learn and adapt to work are the skills majority of novice employees faced difficulty to demonstrate. It was also found out that the curricular learning objectives and learning experiences aren’t relevant and sufficient enough to prepare students in those needed work skills and competencies. Thus, it is concluded that the curriculum isn’t relevant enough to equip students with the competencies required in the world of work. Possible implications of these and other findings of the study have been identified. Key words: Competencies, curriculum, secondary education, work skills, world of work